(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this study was to evaluate the relationship between temporomandibular disorders, mood status and serotonin transporter (5-HTT) gene polymorphisms in Syrian population. Twenty patients with temporomandibular joint disorder (TMD), and 36 healthy control subjects were examined. The sample consists of 23 males, and 33 females aged between (19-30 years old), visited the department of fixed prosthodontic of the faculty of dentistry, Damascus University. This study shows that S/L allele of 5-HTTLPR was the most frequently observed allele in TMD patients; whereas statistical analysis did not show significant difference between patient and control groups by neither genotype distribution analysis nor allele frequency analysis. S§ allele analysis showed a relation between it and mood status. Although the study did not show significant relation between TMD and serotonin transporter polymorphism gene, but according to the importance of serotonin transporter polymorphism gene and its relation to psychological factors we suggest other studies which focus on the relation between the genetics, psychology and TMD.